UPAYA GURU DALAM MENANGANI ANAK BERKEBUTUHAN KHUSUS DI TK FAMILY FEST KOTA BANDUNG - Nurfadhillah, Rahma (2015)
Most special need pre-school age students haven't got the education in pre-school yet. This happened because the existence of pre-school education hasn't been able to give some services that is suitable with their need. To give services to special need pre-school age students, the pre-school education that has been exist should be able to give services to special need students. The service of pre-school age education that gives service not only to normal students but also to special need students colled inclusive pre-school age education. Inclusive education is an education existing all students in a kind of learning process by holding an education giving chance to all students to study together in a certain learning process that is suitable with the need of every students without thingking about the ethnic, race, social statue, economic condition, language, place, sex, religion and differentiation of mental and physical condition. Key words: The right of children, Pre-school age students, Inclusive education. Anak berkebutuhan khusus berhak mendapatkan layanan pendidikan. Anak berkebutuhan khusus ada di masyarakat belum semuanya mendapatkan layanan di pendidikan anakberkebutuhan khusus . Hal ini disebabkan karena keberadaan pendidikan anak usia dini belum mampu memberikan pelayanan sesuai dengan kebutuhannya. Untuk memberikan pelayanan anak berkebutuhan khusus usia dini maka pendidikan anak usia dini yang telah ada